Usage and Gratification of Social Media in Higher Education: A Survey on the Perceptions of International Students in Turkey - (:unkn) unknown (ONLINE JOURNAL COMMUNICATION & MEDIA TECHNOLOGIES-OJCMT, 2017)
This study grounded in the user centered media theory of uses and gratification; it investigated on the usage and gratification of social media among international students pursuing higher education in Turkey, through a survey conducted on a sample of international students in Istanbul City, Turkey. The study was quantitative in nature in which structured questionnaires were used to get data on a randomly selected sample. Findings indicate that 68.2% of the respondents used social media for more than twice a week to interact with peers for studying outside classroom. Likewise, social media platform commonly used included YouTube, Facebook, WhatsApp, Google group and Twitter. As a gratification, the respondents used You Tube to watch educational video clips on lectures delivered from other universities, watched Turkish videos to improve on their Turkish language skills. Facebook and Whatsapp were used for instant messaging, sharing academic information with classmates and professors. Findings indicate that using Social Media positively influenced their lifestyles and helped them to excel academically as reflected in the responses. The study therefore concludes that Social Media is an essential communication tool among international students in Turkey in supporting their higher education.
Keywords: Social Media; Gratification; International Students; Education; Turkey